Safeguarding Osteointegration in Diabetic Patients: A Potent "Chain Armor" Coating for Scavenging ROS and Macrophage Reprogramming in a Microenvironment‐Responsive Manner. (27th May 2021) - He, Qingqing; Yuan, Shuai; Tang, Han; Wang, Si; Mu, Zhixiang; Li, Dize; Wang, Shan; Jing, Xuan; Hu, Shanshan; Ji, Ping; Chen, Tao
Abstract: Risk of implant failure increases profoundly in patients with pre‐existing conditions (e.g., diabetes). Current therapies adopt a one‐sided focus on the direct antibacterial properties of biomaterials and osteogenesis stimulation. However, in this study it is demonstrated that a "chain armor" structure (Ce‐TA) that mainly targets the regulation of the local pathological microenvironment, provides a novel solution to scavenge reactive oxygen species (ROS) by simulating superoxide dismutase and catalase and significantly improving osteointegration under diabetic conditions. Ce‐TA based on a metal phenolic network biological functional interface is successfully constructed. Ce‐TA, an ultrathin armor structure, is biocompatible and facile. Through in vitro assays it is demonstrated that Ce‐TA reshapes the diabetic microenvironment into a regenerative one in a microenvironment‐responsive manner, where Ce‐TA regulates hypoxia‐inducible factor 1α (HIF‐1α) activity by reducing the level of mitochondrial ROS, and effectively alleviates mitochondrial dysfunction and reprogrammes macrophages to a pro‐healing state. Furthermore, it is confirmed that Ce‐TA shows excellent therapeutic effects on the reducing postoperative infection and enhances osteointegration of intra‐osseous implants in diabetic rat models. The proposed strategy opens up a promising opportunity for repurposing metals with intrinsic enzyme‐like activity for the goal of enhancing the osteointegration of devices with orthopedic and dental applications among diabetic patients. Abstract : A novel solution to improve diabetic osteointegration through correcting the pathological microenvironment is reported here. Cerium‐tannic acid, in a microenvironment responsive manner, scavenges excessive mitochondrial reactive oxygen species by simulating superoxide dismutase and catalase. This strategy provides a new approach to endow metals with enzyme‐like activity for improving osteointegration among diabetic patients with orthopedic and dental devices.